2010
DOI: 10.1007/s11366-010-9130-2
|View full text |Cite
|
Sign up to set email alerts
|

Building China’s Soft Power for a Peaceful Rise

Abstract: With China's rapid economic progress and steady increase in its international influence, China has gradually embarked on the soft power idea and has made developing its soft power as its national strategy. We argue that China's soft power strategy is in accordance to Chinese Confucian culture and political value and fits well with its grand strategy of peaceful rise. Based on existing conceptualizations of soft power, we expanded the sources of soft power to six pillars: cultural attractiveness, political valu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(19 citation statements)
references
References 10 publications
0
19
0
Order By: Relevance
“…Currently, there are more than 300 Confucius Institutes all over the world, including one in Malaysia (Xinhua News Agency 2010). Several researchers have described these efforts as China's aspiration to enhance and exercise its 'soft power' (Ding and Saunders 2006, Hartig 2012, Huang and Ding 2006, Li and Worm 2011, Zhao and Huang 2010. 'Soft power' is a concept developed by Joseph Nye (1990) and it refers to the ability of a country to use its attraction rather than coercion to influence other countries' policies in order to achieve the desired results.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, there are more than 300 Confucius Institutes all over the world, including one in Malaysia (Xinhua News Agency 2010). Several researchers have described these efforts as China's aspiration to enhance and exercise its 'soft power' (Ding and Saunders 2006, Hartig 2012, Huang and Ding 2006, Li and Worm 2011, Zhao and Huang 2010. 'Soft power' is a concept developed by Joseph Nye (1990) and it refers to the ability of a country to use its attraction rather than coercion to influence other countries' policies in order to achieve the desired results.…”
Section: Introductionmentioning
confidence: 99%
“…A search of popular mass media and the Internet revealed that people in Western countries hold rather narrow and stereotypical views about China. For example, some still believe that streets in Chinese cities are filled with red lanterns, that people in these streets wear traditional clothes and that everyone pursues Conñician values (Li andWorm 2011, Roel! 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Others are concerned that maybe china could use it as a strategy to dominate and re-draw the world economic and security order through the initiatives instead of continuing with its development philosophy of peaceful development [23]. While Some scholars believe that through this initiative China can choose to be a responsible great power or challenger to the U.S existing hegemony [24], other scholars have emphasized that this is just a strategy of counter-balancing the U.S Asia-Pacific Pivot and Rebalancing Strategy [25].In relation to the NMSR being described as a an opportunity for ASEAN to access economic and financial benefits, this paper will evaluate what elements of hard power and DOI: 10.9790/0837-2201014552 www.iosrjournals.org 49 | Page soft power could be distinguished out of the implementation of this development initiative.On the claim that the NMSR is a response to the U.S's Asia-Pacific pivot, this paper will attempt to evaluate whether the deployment of hard power and soft power strategies by China is for purposes of developing and exercising its economic, security and political influence over ASEAN and other players in the South China Sea Region. To this effect, it becomes necessary to explore and understand whether we could isolate both hard power and soft power mechanisms within the strategic smart power of China being exercised through the NMSR.…”
Section: IIImentioning
confidence: 99%
“…8 Secondly, the work of CIs in developing soft power is still being explored. Despite the proliferation of 339 CIs spread across 83 countries since the first CI was established in 2004, and predictions of more than 1,000 by 2020 (Zhao and Huang, 2010, p. 129), Li and Worm (2010) suggest that China's cultural soft power is in fact underdeveloped, and that CIs can be a coordinating agency for the international advancement of China's cultural strategy and the application of its cultural resources.…”
Section: Peta Saltermentioning
confidence: 99%